PERAN CADANGAN BERAS DARURAT DI KAWASAN ASIA TENGGARA (Forum Penelitian Agro Ekonomi, 2016)
Nowadays, negative impact of climate change on global food provision is apparent. As a disaster-prone region, ASEAN member countries in collaboration with Japan, Republic of Korea and the PRC have established a regional rice reserve named APTERR in 2012. Experts have split opinions regarding the benefit of regional rice reserve. Some experts argued that market is an efficient institution in distributing food, even in times of crisis. Meanwhile, other experts argue that relatively small and decentralized reserves are effective in coping with the problems of food insecurity in the region. Indonesia can view APTERR as an addition sources to the Government Rice Reserve in handling emergency needs, and in solving food insecurity issues. After a long formation process, APTERR has had appropriate mechanisms in operating a regional rice reserve. The challenge is to make APTERR becomes a more effective and efficient institution, and plays important role in maintaining stable rice price and supplies in the region.